Pneumonia due to Enterobacter cancerogenus infection - Demir, Tülin; Baran, Gamze; Buyukguclu, Tuncay; Sezgin, Fikriye Milletli; Kaymaz, Haci (Folia microbiologica, 2014)
Enterobacter cancerogenus (formerly known as CDC Enteric Group 19; synonym with Enterobacter taylorae) has rarely been associated with human infections, and little is known regarding the epidemiology and clinical significance of this organism. We describe a community-acquired pneumonia case in a 44-year-old female due to E. cancerogenus. Identification and antimicrobial susceptibility of the microorganism was performed by the automatized VITEK 2 Compact system (bioMerieux, France). The clinical case suggests that E. cancerogenus is a potentially pathogenic microorganism in determined circumstances; underlying diseases such as bronchial asthma, empiric antibiotic treatment, wounds, diagnostic, or therapeutic instruments.
Keywords: dospělí; Community-Acquired Infections; antibakteriální látky; Adult; Enterobacter; lidé; infekce získané v komunitě; Anti-Bacterial Agents; pneumonie; Humans; Enterobacteriaceae Infections; enterobakteriální infekce; Pneumonia; ženské pohlaví; Female